RATLARA DENEYSEL OLARAK UYGULANAN FARKLI DOZLARDAKİ KURŞUN ASETATIN ARGİNAZ ENZİMİ AKTİVİTE DÜZEYLERİNE ETKİSİ VE ARGİNAZ ENZİMİNİN KİNETİK ÖZELLİKLERİ - DEMİR, FATİH (Fırat Üniveristesi, 2014)
Kent yaşamında ve kurşun kullanan endüstri dallarında kurşuna maruziyet oluşmakta, sonuçta akut veya kronik zehirlenmeler görülmektedir. Günümüzde kırsal bölgelerde su ve besinlerle birkaç mg kurşun alınmaktadır. Kentlerde bulunan endüstriyel artıklar ve motorlu araç egsozlarından yayılan kurşun canlıları etkilemektedir. Kurşun maruziyeti tüm toplumu etkilemekte ve çeşitli sağlık problemlerine yol açmaktadır. Üre siklusunun son enzimi olan arginaz (L-arginin üre hidrolaz veya amidinohidrolaz (E.C 3.5.3.1)), arginini, ornitin ve üreye hidrolize ederek, özellikle memelilerde karaciğerde amonyağın zehirsizleştirilmesinden sorumludur. Karaciğer, arginaz aktivitesinin en yüksek olduğu organdır. Ekstra hepatik dokulardaki aktivitesi, karaciğerden belirgin olarak daha düşüktür. Biz de çalışmamızda kurşun asetatın karaciğer dokusunda bulunan arginazın aktivitesine etkisini araştırdık. Çalışmada ortalama 8 haftalık 28 adet 250 +/- 50 gram ağırlığında Wistar cinsi albino rat kullanılmıştır. Örnekler rastgele alınarak dört gruba ayrılmıştır. Grup I; kontrol grubu 1 ml serum fizyolojik i.p , Grup II; kurşun asetat 25 mg/kg-i.p , Grup III; kurşun asetat 50 mg/kg-i.p , Grup IV; kurşun asetat 75 mg/kg - ip şeklinde düzenlenmiştir. Kurşun asetat 1 ml serum fizyolojik içerisine katılarak 7 gün boyunca sabah akşam birer kez olmak üzere periton içi uygulanmıştır. Deney sonunda tüm gruplardaki ratlara ketamin 75 mg/kg+xylazine 10 mg/kg periton içi (i.p) uygulanarak denekler anestezi altında dekapite edilmiştir. Dekapitasyonun ardından ratların karaciğer dokuları hızla çıkarılarak 0,9 luk NaCI ile yıkanmış, daha sonra paketlenerek soğuk zincirde laboratuvara ulaştırarak -80 °C de derin dondurucada saklanmıştır Rat karaciğer doku arginazı için preinkübasyon ısısı 65°C, preinkübasyon zamanı 20 dakika, inkübasyon zamanı 18 dakika ve optimum pH 10 olarak saptanmıştır. Enzim en yüksek aktiviteyi 3 mM MnCl2 konsantrasyonunda vermiştir. Sonuç olarak enzimin aktivasyonu için Mn+2 iyonlarının ve 65 °C' de preinkübasyonun gerekli olduğu tespit edilmiştir. Kurşun içeren rat karaciğer doku arginazının L- arginine karşı olan Km'inin 8,5 mM civarında, kontrol grubunun ise 11,5 mM civarında olduğu bulunmuştur. Sonuç olarak, Pb varlığında Km ve Vmax nun azaldığı gözlenerek meydana gelen inhibisyonun unkompetatif solduğu bulunmuştur. Anahtar Kelimeler: Kurşun Asetat, Arginaz, Rat

THE EFFECTS OF EXPERIMENTAL APPLIED TO DIFFERENT DOSES LEAD-ACETATE IN RATS ON ARGINASE ACTIVITY AND KINETIC PROPERTIES OF THE ARGINASE ENZYME In the city life and the industrial branches which lead is used, an exposure to lead occurs and as a consequence acute or chronic poisonings are observed. Nowadays, in rural regions few mg of leads are taken with food and water. The lead spreading from the industrial wastes and exhaust of the motor vehicles has an effect on creatures. The lead exposure affects all society and causes various health problems. Arginase which is the last enzyme of the urea cycle ( L-arginine urea hydrolase or amidohydrolase (E.C 3.5.3.1) is responsible for the detoxification of the liver and ammoniac in mammals by hydrolyzing arginine to ornithine and urea. The liver is the organ which has the highest arginase activity. Its activity in extra-hepatic tissues is distinctly lower than liver. We have examined the effect of the lead acetate on the arginase activity found in the liver tissues. In the experiment, 28 Wistar type albino rats were used with the weight of 250 +/- 50 grams and approximately 8 weeks old. The samples were randomly taken and divided into four groups. The groups are regulated as follows; Group I: control group 1 ml physiological saline solution i.p, Group II. Lead acetate 25 mg/kg-i.p Group III: Lead acetate 50 mg/kg-i.p Group IV: lead acetate 75 mg/kg- ip The lead acetate has been added into 1 ml physiological saline solution and during 7 days it was applied in peritoneum one per night and day. At the end of the experiment 10 mg/kg peritoneal spread was applied into 75 mg/kg+ xylazine to the rats in all groups under the anesthesia. Following the decapitation, the liver tissues of the rats are displaced rapidly and were washed with % 0,9 NaCI and were storage in deep freezer at 80 °C C by being packaged and taken to laboratory in cold chain. The preincubation temperature for rat liver tissues was determined as 65 °C and the preincubation time as 20 minutes , incubation time as 18 minutes and optimum pH as 10. The enzyme has given the highest activity in 3 mM MnCI2 concentration. As the result, it is determined that Mn+2 ions and preincubation at 65 °C is required for the activation of the enzyme. It is observed that Km of the rat liver which is opposite to L-arginine of tissue arginase including lead is approximately 8,5 mM and control group is approximately 11,5 mM. As the result, it is observed that Km and Vmax in the presence of Pb causes uncompetitive inhibition by decrasing. Key Words: Lead acetat, Arginase, Rats
The effects of experimental applied to different doses lead-acetate in rats on arginase activity and kinetic properties of the arginase enzyme
Keywords: Biyokimya